The developmental quality of participation experiences: Beyond the rhetoric that "participation is always good!" - Pedro D. Ferreira (2012)
A powerful rhetoric regarding the importance of adolescents' civic engagement and political participation is common in contemporary societies, whilst citizens, both adolescent and adults, seem to express a growing scepticism and alienation regarding politics. Even if this disengagement is debatable, as there are simultaneous signs of an increasing involvement in a variety of emerging and broadly-defined civic and political activities, we argue that the benefits of these experiences should be scrutinized using psychological evidence-based criteria. We rest on classical contributions from developmental psychology, educational theory and political science to define criteria that could inform the quality of participation experiences, and then present two studies that explore its adequacy. Study 1 is a cross-sectional study that observes that higher quality civic and political experiences are connected with more complex modes of thinking about politics. In Study 2, a two-wave longitudinal design, the quality of participation experiences is a significant predictor of change patterns of political attitudes; moreover, results support the argument that participation is not good in itself and that some experiences, with lesser developmental quality, might have a detrimental effect on adolescents' political development. (C) 2011 The Foundation for Professionals in Services for Adolescents. Published by Elsevier Ltd. All rights reserved.